A meta-analysis of four randomized clinical trials to confirm the reliability and responsiveness of the Shortness of Breath with Daily Activities (SOBDA) questionnaire in chronic obstructive pulmonary disease. Issue 1 (December 2015) - Tabberer, Maggie; Brooks, Jean; Wilcox, Teresa
Abstract Background Chronic obstructive pulmonary disease (COPD) is characterized by non-reversible airflow limitation. A common symptom of COPD is dyspnea or shortness of breath. Dyspnea may vary daily, with a large impact on patients' lives. Previous clinical trials used patient-reported outcome (PRO) measures that quantified dyspnea at discrete intervals and hence did not reflect this variability. Recently the Shortness of Breath with Daily Activities (SOBDA) questionnaire was developed as a PRO measure of dyspnea utilizing a daily diary. This confirmatorypost hoc meta-analysis of SOBDA data from a large clinical study program further supports the questionnaire and clarifies the minimum threshold of SOBDA response. Methods Data from four clinical trials (DB2113361, NCT01313637; DB2113373, NCT01313650; DB2113360, NCT01316900; DB2113374, NCT01316913) were analyzed. These 24-week trials were randomized, blinded studies investigating the efficacy and safety of several COPD treatments. Thesepost hoc analyses focused on the SOBDA questionnaire properties. This electronic-diary consists of 13 items completed daily, in which patients rate their breathlessness level during common daily activities. Resultant SOBDA scores were compared with related, commonly used assessments: modified Medical Research Council Research Dyspnea Scale (mMRC), Baseline Dyspnea Index (BDI), Transition Dyspnea Index (TDI), St George's Respiratory Questionnaire (SGRQ), COPD Assessment Test (CAT), and trough forced expiratory volume in 1 s (FEV1 ). The consistency, reliability, validity (convergent, known groups), and responsiveness of the SOBDA questionnaire was assessed. Results In total, 4967 patients with COPD provided data for these analyses. The SOBDA questionnaire had high internal consistency (Cronbach's alpha = 0.936), high test-retest reliability (Pearson's correlation coefficient = 0.86) and convergent validity with related measures (SGRQ total score, Pearson's correlation coefficient = 0.59; CAT, Spearman rank-order correlation coefficient = 0.50). SOBDA scores were statistically significantly lower in responders (as defined by TDI, SGRQ, CAT, and trough FEV1 levels) versus non-responders (p  < 0.001 for all assessments and all time points). Using an anchor-based method, the threshold of a minimum response was calculated as a SOBDA score change of −0.2 (SOBDA score range = 1–4). Conclusions The reliability, validity, and responsiveness of the SOBDA questionnaire as a PRO measure to quantify dyspnea was supported in a large clinical trial population of patients with moderate–very severe COPD.